Factors affecting mental illness and social stress in students using fuzzy TOPSIS / Izleen Ibrahim, Nurul Hidayah Mansor and Jasmani Bidin - Ibrahim, Izleen; Mansor, Nurul Hidayah; Bidin, Jasmani (UiTM Cawangan Perlis, 2022)
A disorder known as mental illness alters a person's emotions, thoughts, or behaviour. Any of these elements alone or in combination may cause it. If stress cannot be managed, people of all ages, races, religions, sexes, and nationalities can develop mental illnesses. The development of mental diseases is significantly influenced by stress. Risk factors for mental illness and social stress include academic stress, socioeconomic position, and financial difficulties. All of these risk variables are challenging to pinpoint because they come from many environments. The purpose of this study is to identify the key aspects that students experience that contribute to mental illness and social stress, as well as to rank those factors by using Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This study ranks social life, academic life, and financial status as the three factors that have the greatest influence on mental illness and social stress among college students. The following evaluation criteria are used to grade the components: family background, educational attainment, physical health, and mode of study. Additionally, Fuzzy TOPSIS is used to rank the variables according to correlation. The issues in this study are evaluated by three decision-makers using linguistic characteristics ranging from "very affected" to "not affected". With a proximity value of 0.469, the research demonstrates that academic life has a significant impact on student's mental health and social stress. With a closeness coefficient of 0.358, social life is the least significant factor. The results of this study may be useful to many people, including parents, counsellors, and the kids themselves. The project's scope could be expanded in the future by adding a range of criteria and options.